2017
DOI: 10.4103/0019-5154.198049
|View full text |Cite
|
Sign up to set email alerts
|

Desert dermatoses (Thar desert, India)

Abstract: Desert dermatology describes the cutaneous changes and the diseases affecting those living in the desert. Diurnal variation in temperature is high and is characteristic of the deserts. The lack of water affects daily activities and impacts dermatological conditions. Adaptation to the desert is, therefore, important to survival. Infections are the most common conditions seen among this population, and among them, fungal infections are the most common. The high incidence of these infections would be accounted fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…In another study[4] involving 327 patients from same geographical region, the authors reported this scaly dermatosis over areas of skin covered with clothing. Interestingly in all study participants, they found an irritant reaction to patient's own sweat when patch test was performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another study[4] involving 327 patients from same geographical region, the authors reported this scaly dermatosis over areas of skin covered with clothing. Interestingly in all study participants, they found an irritant reaction to patient's own sweat when patch test was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Till date various triggering factors have been thought to play a role in causation of sweat dermatitis; most of them emphasize the role of profuse sweating, friction, prolonged exposure of sweat-soaked clothing or undergarment with skin, type of clothing material (tight, porous, synthetic non sweat absorbent), release of unrinsed detergent from clothing,[4] pooling and retention of sweat. Recently Chatterjee and Vasudevan[6] have proposed role of sweat solutes and clothing material in causation of this peculiar dermatitis.…”
Section: Discussionmentioning
confidence: 99%